Effects of monoamine oxidase inhibitor and cytochrome P450 2D6 status on 5-Methoxy-N,N-dimethyltryptamine Metabolism and Pharmacokinetics - Shen, Hong-Wu (2010)
5-Methoxy-N,N-dimethyltryptamine (5-MeO-DMT) is a natural psychoactive indolealkylamine drug that has been used for recreational purpose. Our previous study revealed that polymorphic cytochrome P450 2D6 (CYP2D6) catalyzed 5-MeO-DMT O-demethylation to produce active metabolite bufotenine, while 5-MeO-DMT is mainly inactivated through deamination pathway mediated by monoamine oxidase (MAO). This study, therefore, aimed to investigate the impact of CYP2D6 genotype/phenotype status and MAO inhibitor (MAOI) on 5-MeO-DMT metabolism and pharmacokinetics. Enzyme kinetic studies using recombinant CYP2D6 allelic isozymes showed that CYP2D6.2 and CYP2D6.10 exhibited 2.6- and 40-fold lower catalytic efficiency (V(max)/K(m)), respectively, in producing bufotenine from 5-MeO-DMT, compared with wild-type CYP2D6.1. When co-incubated with MAOI pargyline, 5-MeO-DMT O-demethylation in 10 human liver microsomes showed significantly strong correlation with bufuralol 1’-hydroxylase activities (R² = 0.98; p < 0.0001) and CYP2D6 contents (R² = 0.77; p = 0.0007), whereas no appreciable correlations with enzymatic activities of other P450 enzymes. Furthermore, concurrent MAOI harmaline sharply reduced 5-MeO-DMT depletion and increased bufotenine formation in human CYP2D6 extensive metabolizer hepatocytes. In vivo studies in wild-type and CYP2D6-humanized (Tg-CYP2D6) mouse models showed that Tg-CYP2D6 mice receiving the same dose of 5-MeO-DMT (20 mg/kg, i.p.) had 60% higher systemic exposure to metabolite bufotenine. In addition, pre-treatment of harmaline (5 mg/kg, i.p.) led to 3.6- and 4.4-fold higher systemic exposure to 5-MeO-DMT (2 mg/kg, i.p.), and 9.9- and 6.1-fold higher systemic exposure to bufotenine in Tg-CYP2D6 and wild-type mice, respectively. These findings indicate that MAOI largely affects 5-MeO-DMT metabolism and pharmacokinetics, as well as bufotenine formation that is mediated by CYP2D6.